2008
DOI: 10.1128/jcm.01207-08
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Associations of Human Parechovirus Respiratory Infections

Abstract: Infections with human parechoviruses (HPeVs) are prevalent in young children and have been associated with mild gastroenteritis and, less frequently, with meningitis and neonatal sepsis. To investigate the involvement of these viruses in respiratory disease, a highly sensitive nested PCR was used to screen a large archive of respiratory specimens, collected between January and December 2007. Respiratory samples had previously been tested for eight respiratory viruses, including respiratory syncytial virus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
204
3
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(219 citation statements)
references
References 33 publications
6
204
3
6
Order By: Relevance
“…Several diagnostic laboratories now screen for HPeV infection and together with the retrospective analysis of archived material, a growing number of HPeV associations with disease have been reported recently (Baumgarte et al, 2008;Benschop et al, 2006aBenschop et al, , 2008bBoivin et al, 2005;De Souza Luna et al, 2008;De Vries et al, 2007;Drexler et al, 2009;Harvala et al, 2008Harvala et al, , 2009Li et al, 2009;Tauriainen et al, 2008;Wakatsuki et al, 2008;Wolthers et al, 2008). A greater understanding of the biology and molecular biology of these viruses is therefore required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several diagnostic laboratories now screen for HPeV infection and together with the retrospective analysis of archived material, a growing number of HPeV associations with disease have been reported recently (Baumgarte et al, 2008;Benschop et al, 2006aBenschop et al, , 2008bBoivin et al, 2005;De Souza Luna et al, 2008;De Vries et al, 2007;Drexler et al, 2009;Harvala et al, 2008Harvala et al, , 2009Li et al, 2009;Tauriainen et al, 2008;Wakatsuki et al, 2008;Wolthers et al, 2008). A greater understanding of the biology and molecular biology of these viruses is therefore required.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, parechoviruses consist of two species: human parechovirus (HPeV) and Ljungan virus (LV) (Johansson et al, 2002;Joki-Korpela & Hyypiä, 2001;Stanway & Hyypiä, 1999;Stanway et al, 2000). HPeVs are frequent infectious agents and although they usually cause mild gastroenteritis and respiratory disease in young children, more serious cases, such as flaccid paralysis, encephalitis and myocarditis, have also been reported, particularly associated with HPeV3 infection (Baumgarte et al, 2008;Benschop et al, 2006a Benschop et al, , 2008bEhrnst & Eriksson, 1993;Figueroa et al, 1989;Harvala et al, 2008Harvala et al, , 2009Joki-Korpela & Hyypiä, 2001). Recently, HPeV1 has also been linked to otitis media (Tauriainen et al, 2008).…”
mentioning
confidence: 99%
“…Similar data were found in studies on stool samples in other European countries (Baumgarte et al, 2008;Tapia et al, 2008), and Asia (Ito et al, 2010;Pham et al, 2010Pham et al, , 2011aWatanabe et al, 2007) where HPeV1 was identified as the most prevalent type, followed by HPeV3. HPeV4 is frequently found in stools as well (Benschop et al, 2008c(Benschop et al, , 2010aBoros et al, 2010;Pham et al, 2011b;Zhong et al, 2011), while HPeV6 seems to prevail as a secondary respiratory pathogen (Harvala et al, 2008). Infections with HPeV2 and 5 are reported sporadically (Benschop et al, 2010a;Ehrnst & Eriksson, 1996;van der Sanden et al, 2008).…”
Section: Epidemiology Of Hpev In Relation To Cns Infectionsmentioning
confidence: 99%
“…The same is described for HPeV4 and 6 (Benschop et al, 2008c(Benschop et al, , 2010aHarvala et al, 2008;Pajkrt et al, 2009). Again, not only in clinical sense, but also from a epidemiological point of view, HPeV3 behaves different from other HPeV types.…”
Section: Epidemiology Of Hpev In Relation To Cns Infectionsmentioning
confidence: 99%
See 1 more Smart Citation